2015
DOI: 10.14416/j.ijast.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Composition and Analysis of Medicinal Herbal Potential of Horsfieldia glabra Warb. Seeds

Abstract: Horsfieldia glabra Warb. is a locally consumed plant indigenous to Chiang Rai Province, Thailand and of late, there has been considerable interest in evaluating its health benefits. The aim of this study was to investigate H. glabra Warb. seeds in order to assess their nutritional properties and its potential as a medicinal herb. In terms of nutritional assessment, the experiment found that H. glabra Warb. seed extract contained 68.24 g per 100 g dry weight of lipids, 7.80 g per 100 g dry weight of protein, 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Phenolic compounds were reported to be highly related with DPPH assay, suggesting that all the phenolic compounds contributed to the antioxidant potential of canola plant, which is consistent with the findings Xi et al (2013) in grape seedling treated by EBL. The relation between increasing of DPPH and vitamin B in the many seeds were reported (Chaichana 2016). It seem, in our results, application of EBL in combination with thiamine enhanced radical scavenging capacity more considerably; there by indicating synergistic interactions of EBL and thiamine for ameliorating oxidative stress generated by Cd (Table 4).…”
Section: Discussionsupporting
confidence: 62%
“…Phenolic compounds were reported to be highly related with DPPH assay, suggesting that all the phenolic compounds contributed to the antioxidant potential of canola plant, which is consistent with the findings Xi et al (2013) in grape seedling treated by EBL. The relation between increasing of DPPH and vitamin B in the many seeds were reported (Chaichana 2016). It seem, in our results, application of EBL in combination with thiamine enhanced radical scavenging capacity more considerably; there by indicating synergistic interactions of EBL and thiamine for ameliorating oxidative stress generated by Cd (Table 4).…”
Section: Discussionsupporting
confidence: 62%
“…Inhibition zone diameter of leaf EO of M. fragrans was determined against pathogenic bacteria and Candida tropicalis by Kirby Bauer method (Mary et al, 2012). Only seven studies and one literature review were found with MIC out of which five studies and the literature review were reported with solvent extracts and essential oil without characterizing the components (Chaichana, 2016;Hu et al, 2005;Q. Liu et al, 2017;Piaru et al, 2012;Shafiei et al, 2012;Vinayachandra & Chandrashekar, 2014).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Inhibition zone diameter of leaf EO of M. fragrans was determined against pathogenic bacteria and Candida tropicalis by Kirby Bauer method (Mary et al, 2012). Only seven studies and one literature review were found with MIC out of which five studies and the literature review were reported with solvent extracts and essential oil without characterizing the components (Chaichana, 2016; Hu et al, 2005; Q. Liu et al, 2017; Piaru et al, 2012; Shafiei et al, 2012; Vinayachandra & Chandrashekar, 2014). However, MIC values (<25 μg/ml) of only two studies may have moderate translational relevance to the human application (Hu et al, 2005; Rangkaew et al, 2009) where the former used only extracts without characterizing the biomarkers and the later did not analyze the results statistically.…”
Section: Pharmacologymentioning
confidence: 99%
“…However, comparing with some previous reports, our fraction still has relatively high antioxidant activity. Study on antioxidant activity derived from H. spicata extracts remained underreported, indeed it comes from other Horsfieldia genus such as H. glabra seed extract with the DPPH IC 50 value of 358 µg/mL [17]. Comparing with our potential fractions, H. glabra had ±23 lower antioxidant activity.…”
Section: Discussionmentioning
confidence: 74%